ANALISIS PENDAPATAN DAN PENGEMBANGAN PRODUK COKELAT MILK PADA UMKM CV XY DI KOTA MAKASSAR - N Nuraeni; St Sabahannur; N Nurliani; Andi Azrarul Amri (JURNAL GALUNG TROPIKA, 2022)
The research aims to analyze chocolate milk's income and product development at CV XY UMKM in Makassar City. The method used in this research is the case study method so that all leaders and employees are taken as respondents. Data collection consisted of observations and interviews with the management and employees of CV XY Business to collect primary data. Data analysis comprised organoleptic tests, financial analysis, production cost analysis, income analysis, B/C ratio analysis, and BEP analysis. The results showed that the level of acceptance of the color of milk chocolate reached 47.5% (liked it), 42.5% (liked it for texture), 30.0% for its taste (liked it very much), and 45.0% for its aroma (liked it). CV XY has produced three types of chocolate products, namely Assorted Flavor Chocolate (jar packaging and mica packaging) and chocolate bars, with a total revenue per month of IDR 32,800,000 each, with a total cost of IDR 26,292,506 and revenue of IDR 6,507,494. Chocolate milk, a development product, requires a total cost of Rp. 2,375,000.-. This amount produces 75 milk chocolate products with a net weight of 100 grams and a price of IDR 31,680/100 g. BEP value of each product per unit and BEP rupiah. Assorted-flavored chocolate in jar packaging has a BEP value of 168 units and IDR 8,416,731. Assorted-flavored chocolate with mica packaging has a BEP value of 168 units and IDR 8,398,108. As the chocolate bar has a BEP value of 45 or IDR 1,561,887, it can be said that CV XY has produced above the Break Even Point value. For product development, namely chocolate milk, CV. For XY to reach the break-even point, it must produce and sell at least 60 units of chocolate milk products or obtain sales proceeds of IDR 4,227,700.-